Advantage in privacy protection by using synchronous video observed treatment enhances treatment adherence among patients with latent tuberculosis infection. Issue 9 (September 2020) - Chen, Szu-Hsuan; Wang, Irene; Hsu, Han-Lin; Huang, Chi-Ching; Liu, Yi-Jun; Putri, Denise Utami; Lee, Chih-Hsin
Abstract: Background: Treatment of latent tuberculosis infection (LTBI) is an important strategy for active disease prevention. Conventional in-person DOT (CDOT) programs are challenged by patient dissatisfaction over problems of convenience and privacy. The present study assessed satisfaction to DOT program and treatment adherence of synchronous video observed treatment (SVOT) programs from patients' perspectives. Methods: A two-part questionnaire was presented to 240 subjects with LTBI who received a 9-month isoniazid treatment regimen along with mandatory DOT monitoring during January 2014 to December 2017. Results: Satisfactions with location arrangement ( p < 0.001), ensuring treatment adherence ( p = 0.027), and privacy issues ( p = 0.005) were superior in the SVOT group. The overall rate of LTBI treatment completion was 91.25%. One (1.25%) and 20 (12.50%) of the participants in the SVOT and CDOT groups, respectively, quit LTBI treatment ( p = 0.008). Development of adverse events [adjusted hazard ratio, aHR 8.01 (3.42–18.79)], and the concern of privacy infringement [aHR 5.86 (2.69–12.76)] by the DOT program independently increase the risk of withdrawal. SVOT program [aHR 0.21 (0.06–0.68)] and a belief in the importance of adherence on treatment efficacy [aHR 0.29 (0.08–0.98)] were independent predictors preventing patients from withdrawing from treatment. Conclusions: A comprehensive patient-centered DOT program enables high treatment adherence for the 9-month isoniazid LTBI treatment. Furthermore, SVOT was associated with superior patients' satisfactions which translate into higher treatment completion rates. As treatment adherence is the key to the efficacy of LTBI treatment, SVOT should be a reasonable supplement for LTBI treatment.